Serotonin 5-HT7 receptor slows down the Gs protein: a single molecule perspective - Petelák, Aleš; Lambert, Nevin A; Bondar, Alexey (Molecular biology of the cell, 2023)
The 5-hydroxytryptamine (serotonin) receptor type 7 (5-HT7R) is a G protein-coupled receptor present primarily in the nervous system and gastrointestinal tract, where it regulates mood, cognition, digestion, and vasoconstriction. 5-HT7R has previously been shown to bind to its cognate stimulatory Gs protein in the inactive state. This phenomenon, termed "inverse coupling," is thought to counteract the atypically high intrinsic activity of 5-HT7R. However, it is not clear how active and inactive 5-HT7 receptors affect the mobility of the Gs protein in the plasma membrane. Here, we used single-molecule imaging of the Gs protein and 5-HT7R to evaluate Gs mobility in the membrane in the presence of 5-HT7R and its mutants. We show that expression of 5-HT7R dramatically reduces the diffusion rate of Gs. Expression of the constitutively active mutant 5-HT7R (L173A) is less effective at slowing Gs diffusion presumably due to the reduced ability to form long-lasting inactive complexes. An inactive 5-HT7R (N380K) mutant slows down Gs to the same extent as the wild-type receptor. We conclude that inactive 5-HT7R profoundly affects Gs mobility, which could lead to Gs redistribution in the plasma membrane and alter its availability to other G protein-coupled receptors and effectors.
Keywords: Receptors, G-Protein-Coupled; receptory serotoninové; receptory spřažené s G-proteiny; Gastrointestinal Tract; Receptors, Serotonin; Serotonin; serotonin; gastrointestinální trakt